PERAN BAPPERIDA DALAM PERENCANAAN PENANGANAN RUMAH TIDAK LAYAK HUNI UNTUK PROGRAM STRATEGIS NASIONAL TIGA JUTA RUMAH DI KABUPATEN SIKKA - Maria Aprianti; Imanuel Wellem; Paulus Juru (Universitas Nusa Nipa Maumere, 2026)
The success of this program is highly influenced by the quality of regional planning coordinated by the Regional Development Planning, Research, and Innovation Agency. This research aimed to identify and analyze the role of the Regional Development Planning, Research, and Innovation Agency in planning the handling of uninhabitable houses, understand the stages of the planning process, and determine the factors that influence its effectiveness. This research used a descriptive qualitative approach through observation, interviews, documentation, and literature study during the internship period in the Infrastructure and Regional Development Division. The results showed that the Regional Development Planning, Research, and Innovation Agency has carried out its functions as a facilitator, verifier, and evaluator by integrating the uninhabitable houses program into the Regional Medium-Term Development Plan, the Regional Government Work Plan, and the Strategic Plans of regional agencies. However, several obstacles were still encountered, including limited budget allocation, delays and inaccuracies in data, inadequate human resource capacity, and suboptimal coordination among stakeholders. Therefore, it was necessary to improve institutional capacity, strengthen information systems, and enhance cross-sectoral synergy so that the planning for handling uninhabitable houses can be implemented more effectively, accurately targeted, and sustainably.